2021
DOI: 10.1001/jamaoncol.2020.5660
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Circulating Tumor Cell Count–Driven vs Clinician-Driven First-line Therapy Choice in Hormone Receptor–Positive, ERBB2-Negative Metastatic Breast Cancer

Abstract: IMPORTANCEThe choice between chemotherapy and endocrine therapy as first-line treatment for hormone receptor-positive, ERBB2 (also known as HER2)-negative metastatic breast cancer is usually based on the presence of clinical features associated with a poor prognosis. In this setting, a high circulating tumor cell (CTC) count (Ն5 CTCs/7.5 mL) is a strong adverse prognostic factor for overall survival and progression-free survival (PFS).OBJECTIVE To compare the efficacy of a clinician-driven treatment choice vs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 25 publications
4
103
0
1
Order By: Relevance
“…Despite the highlighted current analytical and technical limitations of ctDNA detection in early setting, encouraging results are shown by investigations addressing the potential prognostic role of ctDNA detection after primary treatment [27,31] , which suggest considering the detection as a good indicator of MRD. Furthermore, the molecular characterization of ctDNA could act as a versatile, dynamic and not invasive tool of disease characterization that might lead clinicians in the process of treatment choice, anticipating or, in a foreseeable future, even partially replacing the tissue biopsy [46] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the highlighted current analytical and technical limitations of ctDNA detection in early setting, encouraging results are shown by investigations addressing the potential prognostic role of ctDNA detection after primary treatment [27,31] , which suggest considering the detection as a good indicator of MRD. Furthermore, the molecular characterization of ctDNA could act as a versatile, dynamic and not invasive tool of disease characterization that might lead clinicians in the process of treatment choice, anticipating or, in a foreseeable future, even partially replacing the tissue biopsy [46] .…”
Section: Discussionmentioning
confidence: 99%
“…In summary, notwithstanding the potential of CTCs in monitoring treatment response, there is still no solid evidence about their role in driving the treatment intensity as, on the other hand, has been recently suggested in the metastatic setting [46] .…”
Section: Clinical Role Of Ctcs In Early Breast Cancermentioning
confidence: 99%
“…Several clinical trials are currently evaluating strategies of incorporating CTC analysis in informing clinical therapeutic choices [ 30 ]. To date, results are available from the phase III randomized STIC-CTC trial for patients with metastatic ER-positive, HER2-negative breast cancer, which showed the validity of CTC analysis to guide clinical decision-making [ 31 ]. Our results may support the use of CTC counts as a tool to stratify patients in whom greater individualized therapy is currently required during and/or after treatment with palbociclib.…”
Section: Discussionmentioning
confidence: 99%
“…Phase III clinical trials evaluating CTC enumeration with clinical parameters have been published in several cancers including the SWOGS0421, SWOG0500, the STIC CTC and the VISNÚ-1 trial [ 8 , 9 , 10 , 11 ]. While the SWOG0421 and VISNÚ-1 studies used CTC counts to identify patients with worse outcomes or to stratify patients for aggressive treatment, SWOG0500 and STIC CTC were the only two trials to date that were actually designed to determine the clinical utility of CTCs.…”
Section: Introductionmentioning
confidence: 99%
“…While the SWOG0421 and VISNÚ-1 studies used CTC counts to identify patients with worse outcomes or to stratify patients for aggressive treatment, SWOG0500 and STIC CTC were the only two trials to date that were actually designed to determine the clinical utility of CTCs. The STIC CTC trial concluded that CTCs may be a reliable biomarker to guide the choice between first-line chemotherapy or endocrine therapy in metastatic breast cancer [ 10 ].…”
Section: Introductionmentioning
confidence: 99%